The Effort of Fruit Drop Reduction Coffe Robusta (Coffea canephora) by Pyraclostrobin - Wiharyanti Nur Lailiyah; Sutrisno Adi Prayitno (Kontribusia : Research Dissemination for Community Development, 2020)
Robusta coffee (Coffea canephora) is a commodity that has a high economic value among other plantation crops. Coffee is also one of the three non-alcoholic drinks (coffee, tea, chocolate) that is widespread. Indonesia and including a strategic country in the world of international coffee, because Indonesia is the third largest coffee exporting country after Brazil and Vietnam. Coffee productivity in Indonesia averages 11,250 tons per year. The purpose of this study was to study the ability of Pyraclostrobin in coffee fertilization so as to reduce the occurrence of fruit drop and determine the appropriate concentration for the treatment of spraying Pyraclostrobin in fertilization and reduce the occurrence of Robusta coffee fruit drop. This research was conducted in January-September 2016 in the coffee plantation in Tlogosari village, Tirtoyudo sub-district, Malang district which is located at an altitude of 560 m above sea level. The method used in this study was a Randomized Block Design. which consisted of 6 treatments and 4 replications. While the treatment is P0 (without spraying), P1 (Spraying once a week with a concentration of 150 ppm), P2 (Spraying once a week with a concentration of 300 ppm), P3 (Spraying once a week with a concentration of 450 ppm), P4 (Spraying 1 week once with a concentration of 600 ppm), P5 (Spraying once a week with a concentration of 750 ppm). Giving pyraclostrobin with a concentration of 600 ppm can increase the number of fruits compared to the treatment without pyraclostrobin.